Enhanced Oil Recovery Techniques Miscible and Immiscible Flooding - Ali, Abdalla A. M.; Zulkefli, Yaacob; Nour, A. H. (Asian Network for Scientific Information, 2014)
The shortage of oil products in the recent years has evidently proved that Enhanced Oil Recovery (EOR) technologies require great attention in order to offer solutions to the impending energy demands in the coming years. This present study shows the details survey of EOR techniques of oil recovery processes and the possibility of producing more oil at a very cost effective manner in oil reservoirs. More specifically, this study deliberated on EOR techniques for offshore fields. The comparisons between miscible and Immiscible CO2-EOR techniques and the general preview of CO2 will be discussed.